Maternal and Neonatal Outcomes of Syrian Adolescent Refugees and Local Adolescent Turkish Citizens: A Comparative Study at a Tertiary Care Maternity Hospital in Türkiye - Golbasi, Ceren; Vural, Tayfun; Bayraktar, Burak; Golbasi, Hakan; Sahingoz Yildirim, Alkim Gulsah (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: In this study, we aim to compare the maternal and obstetric outcomes between local adolescent Turkish citizens and adolescent Syrian refugees admitted to a tertiary care center in Turkey. STUDY DESIGN: Between January 2014 and December 2019, a total of 57,049 births were performed in our hospital. The study included a total of 6,021 patients aged 19 years or younger pregnancy who gave birth at our hospital. Of this number, 5,164 (1,792 Syrian adolescent refugee cases and 3,372 local adolescent Turkish cases) were live singleton pregnancies. Our primary aim was to compare the maternal and obstetric outcomes between the two groups. RESULTS: In the pregnant refugee women, the maternal age was younger (p<0.001). Hemoglobin and hematocrit levels are significantly lower in Syrian pregnant women (p<0.001 and p<0.001, respectively). Anemia was significantly higher in Syrian refugee pregnant women (p<0.001). The double screening test and triple screening test were significantly lower in Syrian pregnant women (p<0.001 and p<0.001, respectively). Preterm birth rates and late preterm delivery prevalence (34-37 gestational weeks) were significantly higher in the adolescent Syrian immigrants’ compared to the adolescent Turkish locals (p<0.001 and p<0.001, respectively). The average birth weight of the Syrian refugees was lower but the number of low birth weight babies was higher Turkish locals (p=0.010 and p=0.014, respectively). The preterm birth ratio and low birth weight ratio in Syrian adolescents has decreased over the years. CONCLUSION: Syrian adolescent refugees are particularly at risk of early pregnancy, high fertility rate, preterm birth, low birth weight, and anemia. Immigrant women should be provided with fertility, family planning, and training on behavior that protects reproductive health. Syrian pregnant women should be supported to receive services.